Regorafenib–avelumab combination in patients with biliary tract cancer (REGOMUNE): a single-arm, open-label, phase II trial. (February 2022) - Cousin, Sophie; Cantarel, Coralie; Guegan, Jean-Philippe; Mazard, Thibault; Gomez-Roca, Carlos; Metges, Jean-Philippe; Bellera, Carine; Adenis, Antoine; Korakis, Iphigenie; Poureau, Pierre-Guillaume; Bourcier, Kevin; Toulmonde, Maud; et al.
Abstract: Background: Regorafenib has shown substantial clinical activity in patients with advanced biliary tract cancers (BTCs). Preclinical data suggested that this drug modulates antitumour immunity and is synergistic with immune checkpoint inhibition. Patients and methods: This is a single-arm, multicentric phase II trial. Regorafenib was given 3 weeks/4, 160 mg quaque die (once a day) (QD); avelumab 10 mg/kg IV was given every two weeks, beginning at C1D15 until progression or unacceptable toxicity. The primary end-point was the confirmed objective response rate under treatment, as per Response Evaluation Criteria in Solid Tumours 1.1. The secondary end-points included the following: 1-year non-progression rate; progression-free survival (PFS) and overall survival; safety and biomarkers studies performed on sequential tumour samples obtained at baseline and at cycle 2 day 1. Results: Thirty-four patients were enrolled in four centres. Twenty-nine patients were assessable for efficacy after central radiological review. The best response was partial response for four patients (13.8%), stable disease for 11 patients (37.9%) and progressive disease for 14 patients (48.3%). The median PFS and overall survival were 2.5 months (95% confidence interval [CI] [1.9–5.5]) and 11.9 months (95%CI [6.2–NA]) respectively. The most common grade 3 or 4 clinical adverse events related to treatment were hypertension (17.6%), fatigue (14.7%) and maculopapular rash (11.8%). High baseline levels of programmed cell death ligand 1 and of indoleamine 2, 3-dioxygénase expression were associated with improved outcomes. Conclusions: Regorafenib combined with avelumab has antitumour activity in a subset of heavily pretreated biliary tract cancer population. Further investigations are needed in patients selected based on tumour microenvironment features. Clinical Trial registration: NCT03475953. Highlights: Regorafenib and anti-programmed death protein 1 (PD-1)/ programmed cell death ligand 1 antibodies are synergistic in preclinical models. Regorafenib/avelumab regimen is safe in patients with advanced biliary tract cancer. Regorafenib/avelumab regimen is active in a subset of patients. Patients should be selected based on tumour microenvironment features.